Trajectories of Depression Symptoms among Older Youths Exiting Foster Care - Munson, Michelle R. (2010)
The purpose of this study was to determine the trajectories of depressive symptoms as older youths from the foster care system mature while also examining the correlates of these trajectories. Data came from a longitudinal study of 404 youths from the foster care system in Missouri, who were interviewed nine times between their 17th and 19th birthdays. Depression was assessed with the Depression Outcomes Module and the Diagnostic Interview Schedule for DSM-IV. Data best fit a model of three trajectory classes, describing young people (1) maintaining low levels of depressive symptoms (never depressed class, 78%), (2) with increasing symptoms (increasing class, 6%), and (3) with decreasing symptoms (decreasing class, 15%). The increasing depression group was mostly male youths who were working or in school; the decreasing class was mostly highly maltreated female youths exiting the foster care system from residential care, with low levels of employment, and in school. Implications for social work practice are discussed.